Two different volume of local anaesthetic in subarachnoid block for Minipercutaneous Nephrolithotomy in prone position - Shrestha, BR; Khadgi, S; Shrestha, S; Thapa, P (Journal of Kathmandu Medical College, 2012)
Aims: To see the maximum sensory level in supine and prone position after subarachnoid block in patients undergoing Minipercutaneous Nephrolithotomy with two different volumes of local anaesthetic. Methods: Prospective randomized comparative study in 500 patients undergoing Minipercutaneous Nephrolithotomy for finding out the extensiveness of sensory level spread after spinal anaesthesia using two different volumes of local anaesthetic before and after keeping patients in prone position. Patients were divided into two groups: Group A (three ml hyperbaric Bupivacaine) and Group B (four ml hyperbaric Bupivacaine) consisted of 250 patients each. Spinal block was performed in sitting position. Sensory level and hemodynamic measurements were carried out at different time points while patients were on supine and on prone position. Results: Patients attaining T4 sensory level at five minutes in Group B was significantly higher than in Group A (p=0.001). After 10-15 minutes of spinal block, greater number of patients in Group B reached T4 sensory level while being in supine position than those in Group A and the difference was statistically significant (p=0.000). After keeping the patients in prone position for in 10-15 minutes the number of patients reaching T4 level was found to be significantly higher in group A than in Group B (p=0.063). Decrease in heart rate and blood pressure in prone position were significant from baseline value and while during supine (p<0.05). Conclusion: Prone positioning extends the sensory level of subarachnoid block to higher level (T4) when three ml of hyperbaric solution is used. DOI: http://dx.doi.org/10.3126/jkmc.v1i1.7249 Journal of Kathmandu Medical College, Vol. 1, No. 1, Issue 1, Jul.-Sep., 2012 pp.10-15